Hubungan Aktivitas Fisik dengan Daya Tahan Jantung dan Fleksibilitas Punggung pada Lansia di Posyandu Lansia Dong Biru Semarang - Budi Yani, Yayuk; , Isnaini Herawati, S. Fis, M.Sc (2017)
BACKGROUND: Entering the elderly will suffer setbacks physical changes, physical deterioration will be a decrease of muscle mass and flexibility. Changes also occur in the cardiovascular, marked by a change in the anatomy of the heart and blood, decrease in maximum heart rate, increased blood pressure, postural hypotension, changes in heart rate recovery after physical activity. Enough physical activity can help improve the flexibility of your back and be strong heart in pumping blood with just a little effort. PURPOSE: To determine the relationship of physical activity with the flexibility of the back of the elderly, to know physical activity with heart endurance in the elderly in Posyandu. RESEARCH DESIGN: Using a type of cross sectional observational method that aims to measure exposure and outcome at the same time. The population in this study are members of Posyandu "Ngudi Saras" Dongbiru Genuk District of Semarang, who met the inclusion criteria are aged> 55 years in both men and women, already a member posyandu minimum for 2 months, ambulate independently without tools, cooperative. Total sample of 45 people. Results were analyzed using Chi Square. RESULTS: The Chi Square test on the relationship between physical activity with the flexibility of showing the result of p = 0.000 (p <0.05) .Uji Chi Square on the relationship of physical activity with endurance janung shows the results of p = 0.000 (p <0.05) .On Chi square test obtained cell has a value of <5, the merger and test again with Exact Fixer. Exact Test Fixer also p value = 0.000 (p <0.05). From descriptive data, this suggests that there is a significant relationship between physical activity with the flexibility and durability of cardiac backs of the elderly. CONCLUSION: There is a relationship of physical activity with the flexibility back in the elderly, there is a relationship of physical activity with heart endurance in the elderly. Elderly who melakukkan regular physical activity has the flexibility and durability backs good heart. Keywords: Physical activity, flexibility, endurance and elderly heart